Collateral damage? On collateral, corporate financing and performance - Geraldo Cerqueiro; Steven Ongena; Kasper Roszbach (European Central Bank (ECB), 2016)
In this paper, we investigate the economy-wide effects of the collateral channel by exploiting: (i) a legal reform in Sweden in 2004 that reduced collateral values, and (ii) a dataset that covers all incorporated firms in Sweden over the period 2000-2006. We find that the loss in collateral value reduces both the amount and the maturity of firm debt and leads firms to contract investment, employment, and assets. The legal reform may distort investment and asset allocation decisions, as firms that reduce their holdings of assets with low collaterizable value and firms that hold more liquid assets consequently become less productive and innovative. Our results therefore document the potency of a collateral channel outside of a crisis.
Keywords: D22; G31; G32; 330; collateral; differences-in-differences; financial constraints; floating lien; investment